Paraneoplastic anti-N-methyl-D-aspartate receptor encephalitis associated with small cell lung cancer and cytotoxic T-cell-mediated pathology: Case report - Akanuma, Haruna; Iizuka, Takahiro; Abe, Dan; Yoshida, Kenji; Matsuda, Nozomu; Sugimoto, Kotaro; Hashimoto, Yuko; Kanai, Kazuaki (Frontiers in Immunology, 2022)
Anti-N-methyl-D-aspartate receptor (NMDAR) antibodies encephalitis is caused by reversible inhibition of ion channels actions by autoantibodies, and is associated with relatively good prognosis. Pathological findings of NMDAR encephalitis usually do not show neurophagorous nodules, but rare or mild inflammatory infiltration. We report a patient of small cell lung cancer (SCLC) related paraneoplastic encephalitis with NMDAR antibodies, a cytotoxic T-cell-mediated pathology of brain, and rapid clinical course. This case highlights that neuropathological diversity of NMDAR encephalitis may be even broader than previously thought, and that NMDAR antibodies may also be found in various pathological conditions with a vigorous immune response.